The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3171/2013.8.spine12998
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of fibrin and chemical synthetic sealant on dural regeneration and brain damage

Abstract: Object Several materials, such as polyethylene glycol (PEG) hydrogel and fibrin glue, have been used to seal dural incisions after brain and spinal surgeries. Although the use of PEG sealant is gaining popularity, it can be associated with postoperative cerebrospinal fluid leakage and infection. However, the reasons for this association are currently unknown. The present study aimed to investigate the effects of PEG sealant and fibrin glue on wound healing and brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…This also corresponded with higher rates of abscess and granulation tissue formation in the PEG group. [ 14 ] While the current investigation was not sufficiently powered to demonstrate a difference among the difference sealants used, we believe our data corroborates a growing body of literature implicating these agents in wound healing complications. This represents a correlation of spinal fluid leaks with the use of sealant.…”
Section: Discussionsupporting
confidence: 74%
“…This also corresponded with higher rates of abscess and granulation tissue formation in the PEG group. [ 14 ] While the current investigation was not sufficiently powered to demonstrate a difference among the difference sealants used, we believe our data corroborates a growing body of literature implicating these agents in wound healing complications. This represents a correlation of spinal fluid leaks with the use of sealant.…”
Section: Discussionsupporting
confidence: 74%
“…They showed that granulation tissue and abscess formation were significantly more severe with DuraSeal, with a massive infiltration of neutrophils. 32 These studies, along with our results and others, 25,28 may explain the higher rate of certain complications seen when combining Durepair and DuraSeal.…”
Section: Effect Of Graft and Sealant Combinationssupporting
confidence: 79%
“…Other clinical studies have suggested an increased risk of wound infections when BioGlue® is used as dural sealant in cranial surgery, due to a pyogenic and chronic inflammatory response. [25][26][27] Adherus® is an activated PEG and polyethyleneimine hydrogel. PEG hydrogels have been frequently used in medical implants due to their ease of use and potential cytocompatibility.…”
Section: Resultsmentioning
confidence: 99%